FACTORS AFFECTING STUDENTS IN TRANSLATING TEXTS IDIOMATICALLY - Morada Tetty (Journal of Language, Literature and Teaching, 2020)
The discussion of translation used by students has been investigated long time ago in which the setup of the Second Language Development was firstly established, i.e around 1900s. Many Error Analyses on translation have been analyzed by linguists which become the valuable contributions towards the study of translation.This study deals with error analysis of students’ project on translations of English Department of UNIMED so that there could be drawn some factors that make students are in difficulty in translating texts idiomatically. Qualitative method is used in analyzing this study and all the data are taken from students’ projects and worksheets on translation.Among factors that cause students are in difficulty in translating texts idiomatically are less understanding the meanings of the texts, do not fully master the lexicogrammar, do not understand the language concepts, social context, language use, etc. Keywords : Translating texts idiomatically, Error Analysis, Second language Acquisition, First language (L1), Second Language (S2)